Managing Food Waste Behaviour in the Kingdom of Saudi Arabia: Investigating the Role of Social Marketing - Albalawi, Suliman (Curtin University, 2023)
This research investigated the key factors that influenced the food waste behaviour of the people of the KSA. A food waste behaviour model was proposed with moral disengagement at the model’s centre. From a literature review, it was hypothesised that religiosity, hedonic value, frugality and trait cynicism are the antecedents of moral disengagement impacting the food waste behaviour in the KSA. The study further posits that an intervention strategy in the form of a social marketing campaign focused on lowering moral disengagement reduced people’s food waste behaviour.